Surface pressure-area isotherm, optical and electrical properties of P3HT/Nanoparticles thin films by modified langmuir-blodgett technique - Fatin Hana Naning@Zin (Tanjong Malim, 2017)
Surface pressure-area isotherm, optical and electrical properties of P3HT/Nanoparticles thin films by modified langmuir-blodgett technique by Fatin Hana Naning@Zin